2014
DOI: 10.1617/s11527-014-0408-2
|View full text |Cite
|
Sign up to set email alerts
|

The development of polyurethane modified bitumen emulsions for cold mix applications

Abstract: Bitumen emulsions stand for an alternative paving practice to the traditional hot-mix asphalts. In addition, modified bitumen emulsions show a better performance than unmodified ones. This work studies the feasibility of obtaining polyurethane modified bitumen emulsions, in which an isocyanate-functionalized polyol constitutes the bitumen modifier (in varying concentration from 1 to 4 wt.%). Storage stability and high in-service performance are evaluated by means of evolution of droplet size distribution (DSD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…However, in this study, the used polymers were completely manufactured and developed at a local level. In addition, back in 2015, studies [32][33][34] analyzing the efficient use of polyurethane-foam-modified bitumen [35] proposed a completely new approach of developing in situ polymerization of monomers that was derived from PET wastes. In these studies, the materials were replaced by up to 10%.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this study, the used polymers were completely manufactured and developed at a local level. In addition, back in 2015, studies [32][33][34] analyzing the efficient use of polyurethane-foam-modified bitumen [35] proposed a completely new approach of developing in situ polymerization of monomers that was derived from PET wastes. In these studies, the materials were replaced by up to 10%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Three samples were prepared for each of the different percentage of additives added to bitumen. The average stability value of all three samples for each tested proportion was considered for detailed analysis with reference to previously followed procedures [2,10,15,25,34,62,63], as shown in Table 5. The testing of the modified bitumen samples showed that stability and flow value, along with mixing temperatures, were within ranges of up to 40% modification, i.e., PUF 5 and PW 5.…”
Section: Marshall Stability Analysismentioning
confidence: 99%
“…Besides, bitumen emulsion presents a much lower viscosity and can be applied at a temperature as low as 80 °C. A conventional binder is sprayed at 160-200 °C so there is a much more additional risk of fire and explosion [9]. Since the beginning of the evolution in recycling technology, many studies involving EMB formulations and applications have been conducted and published.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, not much waste was used and limited in terms of its application. Carrera et al [9] stated that using recycled polyethylene by up to 5 wt.% improved the bitumen performance at high service temperatures of 60 °C. Carrera et al [10] claimed that a higher content of polymer of 4 wt.% enhanced the resistance to permanent deformation at approximately 60 °C compared with the standard nonmodified bituminous emulsions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Bitumen, a byproduct of crude oil distillation, has been largely used as a binder of mineral aggregates in road paving . The common pavement technique, hot spray chip sealing, requires the bitumen to be applied at a temperature of typically 180 °C, which leads to significant consumption of energy and high levels of carcinogen emissions to the environment during road construction and maintenance operations, which increases risks to the health of the operators . Growing concerns about energy conservation and environmental protection have led to an interest in the production of bitumen emulsions for a number of years.…”
Section: Introductionmentioning
confidence: 99%